CSA and slag: towards CSA composite binders. Issue 3 (6th November 2018) - Bertola, Federica; Gastaldi, Daniela; Canonico, Fulvio; Paul, Geo
Abstract : Green binders, eco-friendly cementitious materials, low embedded carbon dioxide cements: different names for products aimed at reducing the environmental impact of cement production. Calcium sulfoaluminate (CSA) cements offer a valid alternative to ordinary Portland cement (OPC) since they couple the advantages of a lower environmental impact during production with high early-age performance and dimensional stability. Their use is now increasing due to the development of dedicated standard processes. The combination of CSA cement with OPC has been widely investigated and a few products have been developed and are already available on the market. Supplementary cementitious materials (SCMs) are widely used to improve the durability performance and lower the clinker content. High levels of substitution have allowed for improvements of performance indicators in terms of carbon dioxide emissions, but mechanical strengths at early ages can be affected. The combination of sulfoaluminate cement, OPC and SCMs opens the route towards innovative composite binders that offer good mechanical performance and significant reductions in carbon dioxide emissions.